Graft revascularization after a hepatic artery rupture inflicted by a stent - S. E. Grigorev; A. V. Novozhilov; A. M. Manukyan; M. O. Movsisyan; E. G. Grigoryev (Трансплантология (Москва))
Introduction. Graft revascularization in deficient arterial blood flow is usually performed by X-ray endovascular stenting procedure and/or by reconstruction of vascular anastomosis. The most serious complication of catheter intervention is a hepatic artery rupture and the critical ischemia of the liver graft.Objective. To discuss the successful treatment of a hepatic artery rupture which occurred during X-ray endovascular revascularization of the liver graft.Case report. A 48-year-old female patient with advanced alveococcosis underwent orthotopic cadaveric liver transplantation. After restoring the blood flow, it was found to be of low-velocity with RI 0.4 in the common hepatic artery. The gastrointestinal duodenal and splenic arteries were ligated. On the second day, a relaparotomy was performed because of intraabdominal bleeding originated from the parenchyma of the 7th–8th segments. Bleeding was arrested. After 18 hours, a selective angiography revealed stenosis up to 90% in the native hepatic artery. After balloon predilatation, stenting was performed, which accidentally caused the artery rupture. The further treatment included relaparotomy and reanastomosing. The patient was discharged from hospital on Day 19 after transplantation.Conclusion. Low velocity blood flow in the hepatic artery did not meet an adequate level even after the ligation of the gastrointestinal duodenal and splenic arteries. We performed the reconstruction of anastomosis. Another possible approach could be a catheter revascularization. The decision should be made considering the specific disorders of regional blood flow, their origin, and the vascular anatomy. The rupture of the artery in the reported case was caused by disproportionate diameters of the stent and vessel.